Severity Matters: The Differential Impact of Mild versus Severe Portal Hypertension on Post-Hepatectomy Liver Failure — A Systematic Review and Meta-Analysis - Aflis; Ketut Wahyu Ananda Putra; Made Agus Dwianthara Sueta (HM Publisher, 2026)
Background: Post-hepatectomy liver failure (PHLF) remains the principal cause of mortality following liver resection for malignancies, particularly in the context of hepatocellular carcinoma (HCC) and cirrhosis. While portal hypertension (PH) has traditionally been viewed as a monolithic contraindication to surgery, emerging evidence suggests that the risk it confers is heterogeneous. This study investigates the hypothesis that the risk of PHLF is strictly severity-dependent. Methods: A systematic review and meta-analysis were conducted on observational studies involving patients undergoing hepatectomy for liver malignancies. Search strategies targeted studies stratifying outcomes by PH severity (mild vs. severe). Primary outcomes were the incidence of PHLF defined by ISGLS criteria. Data were synthesized using random-effects models to calculate pooled odds ratios (OR). Results: Ten studies comprising 4,978 patients were included. The overall presence of PH significantly increased PHLF risk (Pooled OR 3.12; 95% CI: 2.15–4.53; p<0.001). However, stratification revealed a profound divergence: Severe PH (defined as HVPG ≥10 mmHg or clinically significant varices) was associated with a drastic risk escalation (OR 5.86; 95% CI: 2.19–15.65), whereas Mild PH showed a significantly lower risk profile (OR 2.45; 95% CI: 1.10–5.40). Sensitivity analyses confirmed that non-invasive surrogates for PH performed comparably to invasive hemodynamic monitoring in predicting failure. Conclusion: The risk of PHLF is not binary but graded. Severe portal hypertension represents a prohibitive risk state characterized by hemodynamic intolerance to parenchymal reduction. Conversely, mild portal hypertension constitutes a distinct, manageable clinical entity where liver resection remains safe under optimized conditions. Surgical candidacy should be determined by severity grading rather than the mere presence of portal hypertension.